Optimizing Patient Care Through Radiology Nursing Collaboration: A Comprehensive Review of Best Practices and Challenges - Fatimah Mohammed Ali Alsayed1, Sharifah Ghareeb Hussain Munthiri2, Yahya Abdulrhihm Abdullah Alalwi3, Ahmad Hassan Ahmad Alamri4, Mohammed Mousa Ali Alghubayshi5, Saleh Ali Mohammed Al Amri6 (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Effective collaboration between radiologists and radiology nurses is critical for delivering high-quality, patient-centered care. Combining their unique expertise and perspectives leads to improved clinical decision making, fewer errors, enhanced efficiency, and higher patient satisfaction. However, barriers like role ambiguity, poor communication, and hierarchical dynamics can impede productive teamwork if not proactively addressed. Radiologists may under-utilize nurses if they lack understanding of their capabilities and do not actively seek their input. Meanwhile, nurses may feel marginalized if radiologists view their clinical knowledge as superior. Structured communication channels, egalitarian partnerships, and a culture that values collaboration are essential. Radiology departments must advocate for training in interprofessional competencies and implement processes to support joint working. With mutual respect and appreciation for complementary abilities, radiologists and nurses can work synergistically to optimize care. Proactive efforts to foster positive team dynamics are key to overcoming challenges